Maternal Pre-Pregnancy Obesity and Gestational Diabetes Mellitus Increase the Risk of Childhood Obesity - Mi Jin Choi; Juyoun Yu; Jimi Choi (MDPI AG, 2022)
Previous studies have shown inconsistent results regarding the effects of maternal gestational diabetes mellitus (GDM) and pre-pregnancy obesity (PPO) on childhood obesity. This study aimed to determine the risk for early childhood obesity based on maternal GDM and PPO. This nationwide study used data obtained from the National Health Information Database in South Korea. The participants were divided into four groups based on maternal GDM and PPO, and 1:1 matching was performed. Each group had 1319 participants. A generalized estimating equation model was used to analyze the changes in body mass index percentile of children with age, and simple and multiple conditional logistic regression models were used to compare the prevalence of childhood obesity at 5 years. Children whose mothers had both PPO and GDM, only PPO, or only GDM had a 4.46 (95% CI: 3.28-6.05, p < 0.001), 3.11 (95% CI: 2.27-4.26, p < 0.001), or 1.58 (95% CI: 1.12-2.23, p = 0.010) times higher risk, respectively, of developing childhood obesity than children whose mothers had neither PPO nor GDM. Maternal PPO increases the risk for childhood obesity to a higher degree than maternal GDM, and the presence of both increases the risk even further.